Analisis Motivasi Belajar Siswa dalam Pembelajaran Al-Qur’an Hadis dengan Metode Ceramah di MAN 2 Bukittinggi - Bintan Fadhilah; Yulia Fattia; Havis Ramadhan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The purpose of learning the Quran and Hadith in Madrasah Aliyah is to build students' religious understanding and learning motivation. One method that is still widely used is the lecture method, although it is often seen as a conventional method that can potentially make students passive. However, in practice, the lecture method is still maintained because it is considered effective for conveying conceptual material and a wide range of topics.Previous research generally highlights the weaknesses of the lecture method in learning. In fact, the lecture method, when applied flexibly and combined with other methods, has the potential to remain relevant, particularly in the study of the Quran and Hadith at Madrasah Aliyah (Islamic Senior High School). Research on the application of the contextual lecture method and its relationship to student learning motivation is still relatively limited. Based on these conditions, this study aims to analyze students' learning motivation in Al-Qur'an Hadith lessons using the lecture method, which is applied flexibly at MAN 2 Bukittinggi. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and literature review. The research results are expected to provide an empirical overview of the relevance of the lecture method in increasing students' learning motivation